Toll-Like Receptor 4 Gene Polymorphisms in patients withUrinary Tract Infection - Dr. Hammadi A. Al-Hilaly; Dr. AliN. Salman; Ahmed H. Dakheel (University of Thi-Qar Journal, 2019)
Background: Urinary tract infection (UTIs) are considered to be the most common infections in humans. Aims:The present study aimed to investigate the association between single nucleotide polymorphisms (SNPs) in the toll-like receptor 4 (Tlr4) gene (Thr399Ile) and the incidence of Urinary Tract Infection. Subjects and Methods:A total of 49 patients with Urinary Tract Infection and 25 apparently healthy control were enrolled in this study. Urine samples from patients with UTI was collected in AL-Imam AL-Hussain teaching hospital in Thi- Qar province, during the period from February 2014 to March 2015.. Urinary isolates were identified by conventional methods.DNA was extracted from the blood samples taken from these participants. TLR4 gene was amplified with polymerase chain reaction (PCR) using specific primers. Genotyping of the SNPs of interest was done by restriction fragment length polymorphism (RFLP). Results:The present study was showed 26 (53.06%)isolates Escherichia coli; 9 (18.37%) isolates had Pseudomonas aeruginusa;7 (14.29 %) isolates had Klebsiella pneumonia; 4 (8.16%) had Proteus and 3 (6.12%) isolates had Klebsiellaoxytoca, the results showed the presence of heterozygous in one sample from study group at site 399 (C / T) after using restriction enzyme Hinf1. Conclusion: Escherichia coli was most common causative agent in UTI, Thr399Ile may be considered as a risk factor that increases susceptibility to Urinary TractInfection